Smart Energy Management for Microgrid and Photovoltaic Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Microgrids deliver efficient, low-cost, and clean energy while improving regional electric grid operation and stability. They further provide exceptional dynamic responsiveness for energy resources. A global portfolio of operations centered on the development and deployment of microgrids to increase grid dependability and resilience would therefore assist communities in better preparing for future weather catastrophes and keep the world moving toward a sustainable energy future. Solar photovoltaic systems are seen as a promising renewable resource, and their application in microgrids has grown rapidly in recent years.